Diagnóstico y propuesta de plan de mejora del clima laboral en la empresa Ferretería Orbea Cía. Ltda. , en el periodo de abril a julio 2016. - Izurieta Constante, Juan Sebastian (2017)
This is a work of systematization of the experience on Occupational Psychology, Direction and Management of Staff, specifically labor climate. The main objective was to perform for the first time the diagnosis of labor climate in the company Ferreteria Orbea Cia. Ltda. and based on the results obtained suggest an improvement plan aimed to influence positively on this factor. An inadequate labor climate leads to the presence of organizational effects of negative impact as the stress, low performance, job dissatisfaction, among others; this encourages them to determine the importance of the labor climate in the organizations. This systematization given its vision will be based on the concepts and criteria mentioned by Maria del Carmen Sandoval, Master in Business Administration and Professor and researcher, who believes that every company or organization has its own characteristics and the labor climate is one of them. Research with inductive-deductive method and statistical. With a total population of twenty and four partners, has evaluated the work environment through the implementation of the Organizational Climate Survey at-ARG. The results have shown that from a general analysis of the Labor Climate present in the Ferreteria Orbea Cia. Ltda. is favorable. However, negative values were identified in four factors of analysis (Administrative Policies, Monitoring and Control, Social Relations and Decision Making), which served as a reference for the preparation of the improvement plan. This study will serve as a reference to the company for future assessments of the labor climate.